Nanostructured scaffold as a determinant of stem cell fate. Issue 1 (December 2016) - Krishna, Lekshmi; Dhamodaran, Kamesh; Jayadev, Chaitra; Chatterjee, Kaushik; Shetty, Rohit; Khora, S.; Das, Debashish
Abstract The functionality of stem cells is tightly regulated by cues from the niche, comprising both intrinsic and extrinsic cell signals. Besides chemical and growth factors, biophysical signals are important components of extrinsic signals that dictate the stem cell properties. The materials used in the fabrication of scaffolds provide the chemical cues whereas the shape of the scaffolds provides the biophysical cues. The effect of the chemical composition of the scaffolds on stem cell fate is well researched. Biophysical signals such as nanotopography, mechanical forces, stiffness of the matrix, and roughness of the biomaterial influence the fate of stem cells. However, not much is known about their role in signaling crosstalk, stem cell maintenance, and directed differentiation. Among the various techniques for scaffold design, nanotechnology has special significance. The role of nanoscale topography in scaffold design for the regulation of stem cell behavior has gained importance in regenerative medicine. Nanotechnology allows manipulation of highly advanced surfaces/scaffolds for optimal regulation of cellular behavior. Techniques such as electrospinning, soft lithography, microfluidics, carbon nanotubes, and nanostructured hydrogel are described in this review, along with their potential usage in regenerative medicine. We have also provided a brief insight into the potential signaling crosstalk that is triggered by nanomaterials that dictate a specific outcome of stem cells. This concise review compiles recent developments in nanoscale architecture and its importance in directing stem cell differentiation for prospective therapeutic applications.